Risk Assessment of Cnm-Positive Streptococcus mutans in Stroke Survivors (RAMESSES): Protocol for a Multicenter Prospective Cohort Study - Hosoki, Satoshi; Hattori, Yorito; Saito, Satoshi; Takegami, Misa; Tonomura, Shuichi; Yamamoto, Yumi; Ikeda, Shuhei; Hosomi, Naohisa; Oishi, Naoya; Morita, Yoshiaki; Miyamoto, Yoshihiro; Nomura, Ryota; et al. (Frontiers in Neurology, 2022)
Introduction The role of commensal microbiota in systemic diseases, including brain diseases, has attracted increasing attention. Oral infectious diseases, such as dental caries and periodontitis, are also involved in cerebrovascular diseases and cognitive impairment. Cerebral microbleeds (CMBs) and intracerebral hemorrhage due to small vessel disease (SVD), are presumably associated with a high risk of vascular cognitive impairment and stroke. We previously reported that Streptococcus mutans (S. mutans, the main pathogen of dental caries), harboring the cnm gene that encodes the collagen-binding protein Cnm, is associated with the development of hypertensive intracerebral hemorrhage and aggravation of CMBs. We also proposed a mechanism by which the circulating Cnm-expressing S. mutans causes intracerebral hemorrhage or CMBs; it binds to denuded basement membranes mainly composed of collagen IV through damaged tight junctions or it directly invades endothelial cells, resulting in blood-brain barrier injury. In November 2018, we initiated a multicenter, prospective cohort study (RAMESSES: Risk Assessment of Cnm-positive S. mutans in Stroke Survivors; UMIN Clinical Trials Registry: UMIN000045559) to explore the longitudinal association between Cnm-positive S. mutans and CMBs with comprehensive dental findings, which should determine the effect of Cnm-positive S. mutans in the oral cavity on the risk of CMB development and cognitive decline. Methods Fifteen domestic institutes will be enlisted to enroll 230 patients who have at least one CMB in the deep brain area and develop a stroke within the past year. The prevalence of Cnm-positive S. mutans based on oral specimens and dental hygiene will be examined. The primary outcome is the number of newly developed deep CMBs. The secondary outcomes include the new development of lobar, subtentorial, or any type of CMBs; symptomatic intracerebral hemorrhage or ischemic stroke; changes in cognitive function or frailty; major bleeding; all-cause mortality; and antibody titers against periodontal pathogens. The observation period will be 2 years. Discussion The 2-year longitudinal prospective cohort study is expected to establish the role of Cnm-positive S. mutans in SVD including CMBs and intracerebral hemorrhage from the perspective of the “brain-oral axis” and provide guidance for novel prophylactic strategies against Cnm-positive S. mutans-induced SVD.